2008
DOI: 10.1074/jbc.m802872200
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced RNA Polymerase III-dependent Transcription Is Required for Oncogenic Transformation*

Abstract: RNA polymerase (pol) III transcription, responsible for the synthesis of various stable RNAs, including 5 S rRNAs and tRNAs, is regulated by oncogenic proteins and tumor suppressors. Although it is well established that RNA pol III-dependent transcription is deregulated in transformed cells and malignant tumors, it has not been determined whether this represents a cause or consequence of these processes. We show that Rat1a fibroblasts undergoing oncogenic transformation by the TATAbinding protein or c-Myc disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
121
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 107 publications
(129 citation statements)
references
References 40 publications
6
121
1
Order By: Relevance
“…Repression of ERα decreases ethanol‐caused induction of Brf1 and Pol III genes (Figs 4 and 6), whereas human sample studies have shown that Brf1 overexpression is significantly linked to ER+ and PR+ statuses of HBC cases (Figs 1 and 4A, Table 1). Increase in transcription of Brf1 and Pol III genes promotes tumor formation (Johnson et al ., 2008; Zhong et al ., 2011), while high Brf1 expression results in shorter survival period for the patients of hepatocellular carcinoma (Zhong et al ., 2016). However, the HBC cases with low Brf1 show worse prognosis, compared to those with high Brf1 expression (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Repression of ERα decreases ethanol‐caused induction of Brf1 and Pol III genes (Figs 4 and 6), whereas human sample studies have shown that Brf1 overexpression is significantly linked to ER+ and PR+ statuses of HBC cases (Figs 1 and 4A, Table 1). Increase in transcription of Brf1 and Pol III genes promotes tumor formation (Johnson et al ., 2008; Zhong et al ., 2011), while high Brf1 expression results in shorter survival period for the patients of hepatocellular carcinoma (Zhong et al ., 2016). However, the HBC cases with low Brf1 show worse prognosis, compared to those with high Brf1 expression (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…tRNA and 5S rRNA control the translational and growth capacity of cells (Goodfellow et al ., 2006; White, 2004). Studies have indicated that oncogenic proteins, such as c‐Myc, c‐Jun, c‐Fos, and Ras, increase Pol III gene transcription (Goodfellow et al ., 2006; Johnson et al ., 2008; Zhang et al ., 2011, 2013; Zhong and Johnson, 2007; Zhong and Johnson, 2009; Zhong et al ., 2011). In contrast, tumor suppressors, such as BRCA1, p53, PTEN, and pRB, decrease transcription of these genes (Johnson et al ., 2008; White, 2004; Woiwode et al ., 2008; Zhong et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA pol III products have important functions in protein synthesis, protein trafficking, and RNA processing. Enhanced expression of these genes is a hallmark of human cancers, and this has been shown to be required for cellular transformation and tumorigenesis (1,2). Maf1 is a transcription repressor that was first characterized in Saccharomyces cerevisiae as a central node for repression of RNA pol III-dependent gene expression (3,4).…”
mentioning
confidence: 99%
“…RNA polymerase (pol) 2 III transcribes a variety of small untranslated RNAs, including tRNAs, 5 S rRNAs, U6 RNA, and 7SL RNA. RNA pol III products have important functions in protein synthesis, protein trafficking, and RNA processing.…”
mentioning
confidence: 99%